Human reference microbiome profiles of different body habitats in healthy individuals - Oh, Sujin; Park, Kyoung Un (Frontiers in cellular and infection microbiology, 2025)
This study aimed to establish the human reference microbiome profiles in blood, saliva, and stool of healthy individuals, serving as reference values to identify microbiome alterations in human disease. The study population consisted of a reference group of healthy adults and a second group consisting of adults with periodontal disease (PD). Blood, saliva, and stool samples were subjected to 16S rRNA sequencing. Reference intervals of alpha diversity indices were calculated. To reduce the effects of inherent limitations of microbiome data, the taxonomic profiles of the reference group were estimated as log-scaled fold change (logFC) in the abundance of microorganisms between two habitats within the subjects. For stool and saliva microbiomes, differences in the abundances of Firmicutes, Patescibacteria, and Verrucomicrobia distinguished healthy from PD subjects (95% confidence interval (CI) of logFC: [-0.18, 0.31], [-1.19, -0.34], and [-3.68, -2.90], respectively). Differences in the abundances of Cyanobacteria, Fusobacteria, and Tenericutes in stool and blood microbiome of healthy subjects fell within 95% CI of logFC [-0.38, 0.61], [-4.14, -3.01], and [1.66, 2.77], respectively. In saliva and blood, differences in the abundances of Epsilonbacteraeota, Firmicutes, Fusobacteria, and Proteobacteria could be used as reference values (95% CI of logFC: [-3.67, -2.47], [-0.35, 0.49], [-4.59, -3.26], and [-1.20, 0.07], respectively). As the reference microbiome profiles could discern healthy subjects and individuals with PD, a relatively mild disease state, they can be applied as reference values representing the healthy status of the microbiome and for screening of disease states, preferably in preclinical stages.